PENGARUH PEMBERIAN PENDIDIKAN KESEHATAN AUDIOVISUAL TENTANG REPRODUKSI REMAJA TERHADAP PENGETAHUAN PERILAKU SEKSUAL PRANIKAH: EFFECTS OF GIVING AUDIOVISUAL HEALTH EDUCATION ABOUT ADOLESCENT REPRODUCTION TO THE KNOWLEDGE OF PREMARITAL SEXUAL BEHAVIOR - Ranni, Gusti Ayu Indah Puspa; Lestari, R. Tri Rahyuning; Sari, Niken Ayu Merna Eka (Stikes Wira Medika Bali, 2020)
Adolescents are individuals who show the secondary sexual signs until they reach sexual maturity. Maturity of sexual organs and hormonal changes cause the emergence of sexual urges in adolescents in sexual behavior. This study aims to determine the effect of providing health education to the level of knowledge on premarital sexual behavior. This type of research is an experimental quasi-experimental design with a non-equivalent control group design approach. Non-equivalent control group design approach. The number of samples in this study were 94 respondents with stratified random sampling technique. The results showed that 47 (100%) in the treatment group were in the good category while in the control group were 2 (4.0%) in the poor category, 32 (68.0%) in the adequate category and 13 (28.0%) in the good category. Based on the Wilcoxon Signed Rank Test statistical test it is known that p = 0,000 so that p <α nikai α = 0.05, then H0 is rejected, meaning there is an influence of health education. Adolescents are expected to increase their knowledge and understanding of health education, so that they can prevent premarital sexual behavior.